SYSTEM SMART DOOR LOCK PADA RUANG LAB KOMPUTER SMA MUHAMMDIYAH 9 KOTA BEKASI BERBASIS ARDUINO NANO - Muhammad Lukman Hakim; Imam Yunianto; Muhammad Zaenal Mutaqin (Jupiter: Journal of Computer & Information Technology, 2023)
Doors are an important part of any room. Sometimes there is difficulty opening and closing the front door or worrying about manually locking the door. A reliable security system is needed to secure goods or valuables, one of which is by building a security system that uses RFID (Radio Frequency Identification) as an authentication tool so that users who can enter the room can be selected because they have access. Sometimes having trouble opening and closing the front door or worrying about manually locking the door. Technological developments to replace doors with automatic locks also pay attention to the security system. Along with the rapid application of technology, this creates an innovative idea for automatic door safety devices. The purpose of this research is to find a solution to the problem of how to build an automatic door system and door security using RFID (Radio Frequency Identification).